IMPLEMENTASI PEMILIHAN VENDOR SUKU CADANG MOTOR DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Sipayung, Evasaria Magdalena; Prasojo, Thomas Lucky; Sirait, Tamsir Hasudungan (ZONAsi: Jurnal Sistem Informasi, 2023)
MU Bersama Spare Parts Shop is a shop that provides motorcycle spare parts that provides motorcycle spare parts for various types of motorcycles such as automatic, cub, and sport. Motorcycle spare parts products that are sold also vary, including Oil, Spareparts, Body Parts, Tires, and Batteries. Currently, the products in the MU Bersama Motorcycle Parts Shop are around 1000 SKUs. To provide spare parts products needed, MU Bersama Shop ordered products from several motorcycle spare parts vendors. However, shop owners have difficulty in selecting vendors when the vendors who supply certain motorcycle spare parts products cannot provide the products needed so that the shop owners need more time, which is about 1-2 days to determine the vendor of motorcycle spare parts products needed by the shop. This study aims to produce an information system that can be used to assist in the vendor selection process and assist in providing evaluations of vendors based on criteria determined by shop owners including price, quality, accuracy, communication, and availability. The research was conducted using literature review methods, interviews, field observations, data processing and analysis, system design, system implementation, and system testing. The system is designed using the Analytical Hierarchy Process (AHP) method as the calculation method. From the results of the research conducted, it is possible to produce an information system for selecting vendors at the MU Bersama Store with the Analytical Hierarchy Process (AHP) method which is used to help cut the time required in selecting vendors.